Tackling Egypt’s rising food insecurity in a time of transition - Breisinger, Clemens; Al-Riffai, Perrihan; Ecker, Olivier; Abuismail, Riham; Waite, Jane; Abdelwahab, Noura; Zohery, Alaa; El-Laithy, Heba; Armanious, Dina (International Food Policy Research Institute, 2013)
Owing to a succession of crises and worsening poverty, food security in Egypt started to deteriorate as early as 2005. These crises included the avian influenza epidemic in 2006; the food, fuel, and financial crises of 2007-2009; a further rallying of global food prices starting in late 2010; and the challenging macroeconomic context that followed political instability in the wake of the 2011 revolution (see Figure 1). Egypt’s net food-importing status (that includes importing 45-55 percent of its wheat needs) makes it vulnerable to fluctuations in international food prices.